SENTRALISASI DAN DESENTRALISASI DALAM MANAJEMEN MADRASAH IBTIDAIYAH - Juhaeni, Juhaeni (Journal Of Islamic Elementary School (JIES), 2018)
Centralization is the process of administering the state and government that takes place centrally. Decentralization is the surrender of government authority by the government to autonomous regions to regulate and manage self-government in the system of the Republic of Indonesia Unitary State. Decentralization of education will provide full opportunity for education managers to regulate and develop their regions, so that the potential and opportunities of education, especially Elementary School, can develop optimally.